La vita è altrove? L'autunno mediterraneo dei pensionati italiani in Tunisia, tra conflitti e crisi. - Laura Faranda (EtnoAntropologia, 2015)
This text summarizes an ethnographic research started recently in Tunisia, aimed at the recognition of a migratory phenomenon that concerns the Italian retirees. Such exodus involves some questions: is it just a phenomenon which refers to the crisis without precedent of the Italian welfare system? Can we bring this new flow to the dissatisfaction of people who no longer recognize the world in which they lived and who lost their freedom of action and dignity of membership? Can we apply also in this case the canonical meaning of migrant as “atopos”, “displaced”, hybrid, which exists only for defect in the community of origin and for excess in that of reception? With the first data collected, we will attempt to outline some provisional answers and to bring out the anthropological sense of the phenomenon.